Radio Refractive Index structure of upper troposphere over India (MAUSAM, 1967)
The mean monthly values of radio refractive index for 12 radiosonde stations in India based the data during the years 1956.60 have been calculated (at 300,200, 150 and 100-mb levels) and their monthly variation is studied. The distribution of refractive index at 300, 200 and 100-mb levels has been discussed and compared with that of the lower troposphere. during January and August, The variation of the annual range of the index with latitude and altitude is also described.        It is seen that there is a marked difference in the refractive index structure between the lower and upper tropospheres over India. The annual range decreases markedly in the upper troposphere as compared to that in the lower. The range of the index is maximum over the stations in north India at 300 mb and shows similarity with that in the tower troposphere in this respect.